Insights on the elements of democracy - Antonio, Michael G. (2011)
Democracy is seen in many lenses. Within the political science lens, democracy is equated with limited government, freedom, will of the majority and rule of law. Using the same lens, democracy can be broken down to its important elements and with it the elements can be discussed in terms of its strengths and weaknesses. More importantly, the paper provides key opinions on the significance and operational interpretation of democracy within the Philippine societal context. The interpretation of democracy is critical in the way we see ourselves as citizens and the manner in which government functions to serve the needs of the majority. It is along these lines that this paper is anchored on.
Keywords: Democracy